Nikah Malem Songo dalam Bingkai Islam Kultural: Akulturasi Islam dan Tradisi Lokal Masyarakat Pesisir Tuban - Musa’adatul Khoiriyah; Farika Nur Umaisaroh; Nurul Hakim (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the tradition of nikah malem songo within the framework of cultural Islam as a form of acculturation between Islamic teachings and local traditions in the coastal community of Tuban, East Java. The research aims to analyze the acculturation process, identify the religious and cultural values embedded in the tradition, and explore its relevance in contemporary society. A qualitative descriptive approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation involving religious leaders, community figures, and local residents. The findings show that nikah malem songo reflects a harmonious integration of Islamic principles and local cultural practices while maintaining the essential requirements of Islamic marriage. The tradition also contains symbolic elements, such as selecting a sacred time believed to bring blessings. In addition, the practice serves as a social mechanism that strengthens community solidarity, reinforces cultural identity, and transmits values across generations. Although challenged by modernization, globalization, and puritan religious views, the tradition continues to survive through reinterpretation and selective preservation. The study concludes that nikah malem songo represents an inclusive and contextual form of Islam capable of adapting to changing social dynamics.